Lobbyism in Germany: What do we know? - Andreas Polk (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2017)
Based on the two main channels of influence seeking, contribution payments and informational lobbying, we survey empirical studies about lobbying in Germany and discusses the available data and research approaches. Based on two novel data sets, we provide first insights towards further steps of empirical lobbying research. Given the overall lack of available data on lobbying in Germany, we identify research gaps and discuss new methodological approaches which might lead to a better understanding of the lobbying process.
Keywords: D72; D73; K20; 330; Lobbyism; interest groups; economics and law